National anthems of the world - Reed, W. L.; Bistow, M. J. (Blandford Press, 1987)
"In this book, the national anthems of 198 countries are included from Armenia to Zimbabwe, from Palau to Papua New Guinea and from Turkey to Tuvalu." "Each national anthem is presented with the words in the original language(s), which have been set, where possible, to the music and, where a national anthem is in a language that is not written in Roman script, the words are given in a transliterated phonetic version, so that it may be sung by people of other tongues. A literal translation of the original words is also provided. The book also includes a fully revised appendix listing the National Days of each of the countries included in the book."--BOOK JACKET. Presents the national anthems of 198 countries, written for voice and piano, including the national anthem of the new state of Timor-Leste, new words for the national anthems of Antiqua & Barbuda, Belarus, and Ukraine, and new national anthems for Bosniaand Herzegovina, Georgia, and Rwanda.